Research on property variation of silicone rubber and EPDM rubber under interfacial multi-stresses - Liu, Ying; Wang, Xing (IEEE transactions on dielectrics and electrical insulation, 2019)
In this paper, silicone rubber (SR) and ethylene propylene-diene monomer (EPDM) rubber used in 110 kV prefabricated joints of XLPE cables were chosen as subjects, and a multi-stress experimental device was set up to simulate the insulation interface. Different mechanical tensions and/or AC electrical stresses were applied to the rubber samples at the interface composed of XLPE and SR/EPDM. After preset times, microscopic observations, together with measurements of mechanical properties, volume resistivity, crosslinking degree, attenuated total reflectance Fourier infrared spectrum and X-ray photoelectron spectroscopy were performed. It is shown that for both materials, molecular chains are partly broken by electron or ion bombardment from the discharges under electrical stress, and micro-molecules and oxides are formed on the sample surfaces. The mechanical stress facilitates this process without changing the reaction essence. The volume characteristic parameters of SR samples degraded with aging, while those of EPDM samples remained relatively stable. It is shown that under the same interfacial electrical-mechanical stresses, SR samples shows degradation of the overall performance; while for EPDM samples, the damage occurs mainly on the surface. This is due to the different chain structures, filler types and content in the materials.